PENERAPAN LEKSIKON KRAMA INGGIL OLEH GENERASI MUDA BERDASARKAN TINGKAT PENDIDIKAN SEBAGAI IMPLEMENTASI SUBASITA DI KUDUS - Satiti, Sabbihisma Debby (MIMESIS, 2021)
This study examines the application of the krama inggil lexicon by young generation based on education level as a form of implementation of subasita culture in Kudus. This study aims to describe the application of the krama inggil lexicon by today's younger generations, and to interpret the subasita culture that is reflected through the application of the krama inggil lexicon. This research is a qualitative descriptive study with a case study model. This study used 14 informants as data sources. The data of this research are in the form of informants' utterances which are indicated to contain the krama inggil lexicon. The technique of collecting data used observation techniques, listening proficiently, interviewing techniques, recording techniques, note taking techniques and questionnaire techniques. The data analysis technique used a qualitative descriptive technique. The results showed that: 1) the krama inggil lexicon was produced more by the younger generation with middle and lower education level; and Â 2) subasita culture is applied by the younger generation in different ways.